Aplikasi IoT Sistem Monitoring Kualitas Air Tambak Udang Menggunakan Aplikasi Blynk Berbasis Arduino Uno - Gurum Ahmad Pauzi; Mutiara Amalia Syafira; Arif Surtono; Amir Supriyanto (Jurnal Teori dan Aplikasi Fisika, 2017)
The IoT Application in the Shrimp Pond Water Quality Monitoring System has been realized using Arduino Uno Application. This research was conducted to determine of the quality of shrimp pond water using an android smartphone. Sensor input (Temperature, pH and Dissolved Oxygen (DO)) from the sensor readings are processed on Arduino then sent to an android smartphone using ESP8266-01 and measurement result will be displayed on the Blynk Application. The Blynk application will receive water quality data to be displayed in the form of real values or chart. The result obtained that, the system can measure the quality of shrimp pond water using temperature sensor, pH sensor, and DO sensor based on Arduino Uno and control sensors when measuring received data displayed on Blynk application.